HOTOM: a SDN based network virtualization for datacenters - SILVA, Lucas do Rego Barros Brasilino da (2015)
Although datacenter’s server hosts have embraced virtualization, the network’s core itself has not. A virtual network (VN) is an instance (slice) of network resources such as links and nodes that is built on top of a physical network. Indeed, virtual networking is of paramount importance for multi-tenant datacenters, since it makes management easier. However, VLANs continue to be used nowadays, driving virtualized datacenters to scalability constraints. VLAN isolates layer 2 (L2) address spaces and indexes them by a 12-bit value, which imposes the hard limit of only 4,096 VNs. Modern Cloud Computing-aware datacenters have being required for delivering IaaS, and are willing to go beyond these scalability restrictions. Even modern tunneling schemes, such as STT, come at a price of overhead because frames are encapsulated by higher layer protocols (UDP, IP). In addition, current virtualized datacenters demand specialized switching hardware (layer 3), increasing datacenter’s CAPEX, and require huge computing resources in order to precompute virtual link’s states. Recently, the Software-Defined Networking (SDN) appears as a potential solution for fulfilling those needs by enabling network programmability. SDN decouples the network control from the data plane, placing the former in a central controller that exposes an API for developers and vendors. As a consequence, controllers have a unified network’s view and are able to execute custom network applications, reaching an unprecedent flexibility and manageability. OpenFlow is currently the most prominent SDN technology. Even with SDN, many questions remain unanswered. For instance, how to provide scalability and dynamics to a network while preserving legacy core devices? If a datacenter operator can preserve its previous investments, surely he will adopt SDN easier. This dissertation presents HotOM (HotOatMeal), a new virtualized datacenter network approach that, by leveraging SDN, overcomes the traditional scalability constraints, enables network programmability while still using legacy network devices, therefore preserving CAPEX. The logic part of HotOM was implemented in Python programming language as a component of the POX OpenFlow controller. HotOM was deployed and evaluated in a real testbed. Analyses were done, from throughput, RTT, CPU time usage to scalability. These metric results were compared against plain VLAN Ethernet network. In addition, a validation of isolation between tenants was performed, as well as a study on protocol overhead. It was confirmed that HotOM scales up to 16.8M tenants, while achieving 47%, 44%, 41% less overhead than STT, VXLAN, and NVGRE, respectively. Finally a qualitative analysis between HotOM and state of the art datacenter virtual network (DCVN) proposals was carried out, showing by comparison that HoTOM consolidates advantages in many functional features: it fulfills almost all evaluated characteristics, more than any other presented technology.